Ring-fused 3β-acetoxyandrost-5-enes as novel neuroprotective agents with cholinesterase inhibitory properties. Issue 225 (January 2023) - Gonzalez, Gabriel; Kvasnica, Miroslav; Svrčková, Katarína; Štěpánková, Šárka; Santos, Joana R.C.; Peřina, Miroslav; Jorda, Radek; Lopes, Susana M.M.; Melo, Teresa M.V.D. Pinho e
Abstract: Alzheimer´s disease (AD) is an intellectual disorder caused by organic brain damage and cerebral atrophy, characterized by the loss of memory, judgment, and abstract thinking followed by declining cognitive functions, language, and the ability to perform daily living activities. Many efforts have been made to decrease the effects of the disease but also to block the neurodegenerative process. Cholinesterase inhibitors (ChEIs) are a group of medicines that act at the neurotransmission of acetylcholine, preventing its excessive breakdown and helping to improve cognitive functions in patients with AD. In this work, 16 chiral steroids, namely ring-fused 3β-acetoxyandrost-5-ene derivatives, their precursor and two 16-dehydroprogesterone-derived dioximes, were assessed as cholinesterase inhibitors and neuroprotective agents. The results demonstrated that some of the tested steroids are cholinesterase inhibitors and the majority selective for acetylcholinesterase inhibition. Albeit, one ring-fused 3β-acetoxyandrost-5-ene containing N -methylpiperidine ring (compound 2g ) demonstrated to be a selective and potent inhibitor of the butyrylcholinesterase enzyme. ( S )− 4, 4a, 5, 6, 7, 8-(hexahydronaphthalen-2-one)-fused 3β-acetoxyandrost-5-ene (compound 6 ) showed high neuroprotective effect, high ability to restore the mitochondrial membrane potential from glutamate intoxication, and dramatic improvement in cell morphology. The described results provided relevant structure-activity relationship data. Graphical Abstract: ga1 Highlights: Ring-fused 3β-acetoxyandrost-5-ene derivatives and 16-dehydroprogesterone-derived dioximes as cholinesterase inhibitors. The binding mode of 2 g to human BChE was evaluated by molecular docking studies. Ring-fused 3β-acetoxyandrost-5-enes as neuroprotective agents in glutamate-induced model of oxidative damage. Compound 6 displayed neuroprotective properties in lactate dehydrogenase release assay. Derivative 6 displayed protective activity against oxidative stress and induction of caspase-3, 7 activity.